problematika penerjemahan kolokasi dalam kumpulan cerpen "Amiiroh fil Mir'ah" karya Lina Kaylani - Nur Fauziah Fatawi (Jurnal Internasional Pendidikan Bahasa Arab, 2020)
Translator is an effort to move the meaning of the source text into the target language the transfer of meaning related to the message the writer wants to convey. Likewise in the translation of the book Ami>rah Fi> al-Mir'a>h by Lina Kaylani. The problem of translation arises when the collocation is translated by following the original Arabic pattern without adjusting to the target language, be it context, vocabulary, or sentence structure. Collocation is a permanent association between words and other words that coexist in a sentence. Mona Baker states that collocation is a rather flexible language pattern which allows several variations of form. The purpose of this study is to find the collocation expressions (‘Iba>rah al-Mutas}a>h}ibah) and how to translate it. This research results that the researcher found 23 kinds of collocation expressions and has two ways in translating them, as follows; The translator must choose the exact and appropriate words for the collocation expressions in the Arabic language, or the translator must search for their equivalence and the translator must search for the same phrase in the Indonesian language, the phrase in which it is considered accompanying.